RECURRENT LARYNGEAL NERVE INJURY IN TOTAL VERSUS SUBTOTAL THYROIDECTOMY - Sajid, Tahira; Naqvi, Syeda Rifaat Qamar; Naqvi, Syeda Saima Qamar; Shukr, Irfan; Ghani, Rehman (Journal of Ayub Medical College Abbottabad, 2016)
Background: Both Total and Subtotal Thyroidectomy are correct treatment options for symptomatic Euthyroid Multinodular Goitre. The choice depends upon surgeon’s preference due to consideration of disadvantages like permanent hypothyroidism in Total Thyroidectomy and high chances of recurrence in Subtotal Thyroidectomy. Many surgeons believe that there is a higher incidence of Recurrent Laryngeal nerve injury in Total Thyroidectomy which affects their choice of surgery. This study aimed to compare the incidence of recurrent laryngeal nerve injury in total versus subtotal thyroidectomy. Methods: This non randomized controlled trial was carried out at Department of Surgery and ENT of Ayub Teaching Hospital Abbottabad, and Combined Military Hospital Rawalpindi from 1st September 2013 to 30th August 2014. During the period of study, patients presenting in surgical outpatient department with euthyroid multinodular goitre having pressure symptoms requiring thyroidectomy were divided into two groups by convenience sampling with 87 patients in group 1 and 90 patients in group 2. Group-1 was subjected to total thyroidectomy and Group -2 underwent subtotal thyroidectomy. All the patients had preoperative Indirect Laryngoscopy examination and it was repeated postoperatively to check for injury to the recurrent laryngeal nerve. Results: A total of 177 patients were included in the study. Out of these, 87 patients underwent total thyroidectomy (Group-1). Two of these patients developed recurrent laryngeal nerve injury (2.3%). In group-2 subjected to subtotal thyroidectomy, three of the patients developed recurrent laryngeal nerve injury (3.3%). The p-value was 0.678. The overall risk of injury to this nerve in both surgeries combined was 2.8%. Conclusion: There is no significant difference in the risk of recurrent laryngeal nerve damage in patients undergoing total versus subtotal thyroidectomy. Keywords: Total thyroidectomy, subtotal thyroidectomy, recurrent laryngeal nerve injury